2022
DOI: 10.21608/asejaiqjsae.2022.263514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chemical, Microbiological and Sensorial Properties of Yoghurt Fortified with Aloe Vera Gel

Abstract: Yoghurt is one of the most popular fermented dairy products in the world; it has a considerable market share due to its nutritional value as well as its health benefits. The buffalo milk yoghurts used in this study was fortified with varying amounts of either fresh (FAVG) or lyophilized Aloe Vera gel (LAVG). Five treatments used to prepare yoghurt ((T1: Control , T2: 1% (FAVG) , T3: 10% (FAVG) , T4:0.1% (LAVG) , T5:0.2% (LAVG)). The physicochemical, microbiological and sensorial properties of yoghurt treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
6
2
0
Order By: Relevance
“…Treatment A1 got (4.47) % protein, while treatment A5 got (4.49)% protein compared to control group C, which got (4.26)% protein. The results agreed with what was reached by [25] who found that the addition of aloe vera increases the percentage of protein, and these results were similar to what was found by [26], and the results are consistent with what was reached by [27], who showed that aloe vera extract increased the protein percentage of the product. The researcher indicated that the increase in the percentage of protein when the product was fortified was due to the increase in the percentage added by aloe vera gel.…”
Section: Chemical Composition Of Laboratory-produced Yogurt Fortified...supporting
confidence: 92%
See 2 more Smart Citations
“…Treatment A1 got (4.47) % protein, while treatment A5 got (4.49)% protein compared to control group C, which got (4.26)% protein. The results agreed with what was reached by [25] who found that the addition of aloe vera increases the percentage of protein, and these results were similar to what was found by [26], and the results are consistent with what was reached by [27], who showed that aloe vera extract increased the protein percentage of the product. The researcher indicated that the increase in the percentage of protein when the product was fortified was due to the increase in the percentage added by aloe vera gel.…”
Section: Chemical Composition Of Laboratory-produced Yogurt Fortified...supporting
confidence: 92%
“…Compared to the control group C, which had a percentage of fat (3.45%), treatment A1 had a fat percentage of (30.3%) and treatment A5 had a fat percentage of (2.46%). These findings support the findings of [27], who concluded that yogurt IOP Publishing doi:10.1088/1755-1315/1262/6/062023 6 must have a minimum fat concentration of 3% and that the decrease in fat content when aloe vera was added was caused by the enzyme's natural breakdown of milk fat. The yogurt that comes from this study is therefore regarded as low-fat yogurt.…”
Section: Chemical Composition Of Laboratory-produced Yogurt Fortified...supporting
confidence: 87%
See 1 more Smart Citation
“…Treatment A1 got the total number of bacteria (6.46). While treatment A5 obtained the total number of bacteria (4.34) compared to the control group C, which obtained the total number of bacteria (6.82), the results agreed with what was reached [18] in the effect of Olevera extract on the total number of bacteria, as the results showed There is a significant effect between the experimental treatments with the increase in the concentration of the Olevera extract. This may be due to the control of the acidification and fermentation of the yogurt during the storage period, which in turn limits the growth and activity of the total number of bacteria.…”
Section: Microbial Propertiessupporting
confidence: 85%
“…There were no significant differences between the control sample and the samples added to it with different IOP Publishing doi:10.1088/1755-1315/1262/6/062021 4 concentrations of Olevera extract, and this indicates the ability of the Olevera extract to reduce the growth of microbes, as indicated by the researcher [21]. Table (1) also shows the numbers of yeasts and molds, as the experimental samples did not record any growth in relation to yeasts and molds during the storage period, and the results agreed with what the researcher reached [18] that the Olevera gel completely inhibited yeasts and molds, as it was not Discovering any growth during the experiment obtained on the Olevera extract.…”
Section: Microbial Propertiessupporting
confidence: 76%